The volunteer management handbook : leadership strategies for success - Connors, Tracy Daniel (Hoboken, NJ : Wiley, 2012)
"Completely revised and expanded, the ultimate guide to starting--and keeping--an active and effective volunteer programDrawing on the experience and expertise of recognized authorities on nonprofit organizations, The Volunteer Management Handbook, Second Edition is the only guide you need for establishing and maintaining an active and effective volunteer program. Written by nonprofit leader Tracy Connors, this handy reference offers practical guidance on such essential issues as motivating people to volunteer their time and services, recruitment, and more. Up-to-date and practical, this is the essential guide to managing your nonprofit's most important resource: its volunteers.Now covers volunteer demographics, volunteer program leaders and managers, policy making and implementation, planning and staff analysis, recruiting, interviewing and screening volunteers, orienting and training volunteers, and much moreUp-to-date, practical guidance for the major areas of volunteer leadership and managementExplores volunteers and the law: liabilities, immunities, and responsibilitiesDesigned to help nonprofit organizations survive and thrive, The Volunteer Management Handbook, Second Edition is an indispensable reference that is unsurpassed in both the breadth and depth of its coverage"--
Includes bibliographical references and index.
Keywords: Voluntarism -- United States -- Management; Nonprofit organizations -- United States -- Personnel management